A new research approach for religious tourism: the case study of the Portuguese route to Santiago. (10th September 2012) - Fernandes, Carlos; Pimenta, Elsa; Gonçalves, Francisco; Rachão, Susana
Travel related to religious sites and festivals, pilgrimage or spirituality is a long established and extremely important sector of the tourism market. Pilgrimage sites provide an important underpinning to the basic tourism product not only at the pilgrimage destinations but also along the routes leading to them, which often attract those not travelling directly for religious purposes (Richards and Fernandes, 2007). The aim of this paper is to find more about the motivations and consumption patterns of pilgrims on the Portuguese route of Caminos de Santiago. A survey was undertaken by the Tourism Laboratory of the Polytechnic Institute of Viana do Castelo (Portugal). Results suggest that the consumption patterns and consequently the economic impact of pilgrims along the Portuguese route to Santiago de Compostela are minimal.